Mental health terhadap generasi strawberry serta penanganan dalam Islami - Darmayanti, Silvi Nur Afifa (Maliki Interdisciplinary Journal, 2024)
Mental Health is a good emotional event that can provide benefits in emotional abilities and also function in the community, as well as fulfilling the journey of life. The essence of mental health itself is more about maintaining a healthy mentality. Today’s young people are not yet fully able to fulfill the components of ideal character needed to support the progress and success of a nation in the future. Strawberry Generation represents strawberries that are beautiful but easily fragile when stepped on. The birth of the Strawberry Generation was influenced by several factors, including the parenting style of parents in educating and raising their children. Thus, the need for other actions is not only medical treatment but also Islamic treatment such as being patient, getting used to doing things and being disciplined, adopting good and positive habits, increasing confidence in applying the values ​​of truth, beauty, virtue, and faith in reading prayers and understanding verses of the Koran and hadith, and participating in Islamic activities, for example, dhikr assemblies and recitations.